2000
DOI: 10.1210/jcem.85.6.6619
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Monitored Mitotane Treatment Achieves the Therapeutic Range with Manageable Side Effects in Patients with Adrenocortical Cancer1

Abstract: Eight patients with adrenocortical cancer were treated with low doses of mitotane (2-3 g daily) while monitoring drug plasma levels. When the mitotane concentrations reached the therapeutic range (defined as mitotane plasma levels between 14-20 microg/mL), a dose reduction was performed to avoid toxicity. Thereafter, the mitotane dose was tailored according to plasma levels. A progressive increase in plasma mitotane concentrations was observed during treatment, and a highly significant linear correlation was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Tel. : +39 011 6705442; fax: +39 011 9038649. still not clear [7,8]. Adverse reactions are common mainly to the gastrointestinal, central nervous system, and derma, but nontolerable toxic events are rare when the plasma concentration is less than 15 g/ml.…”
Section: Introductionmentioning
confidence: 99%
“…Tel. : +39 011 6705442; fax: +39 011 9038649. still not clear [7,8]. Adverse reactions are common mainly to the gastrointestinal, central nervous system, and derma, but nontolerable toxic events are rare when the plasma concentration is less than 15 g/ml.…”
Section: Introductionmentioning
confidence: 99%
“…The antitumor effect of mitotane is related to the maintenance of adequate plasma drug levels [7][8][9][10]. It is suggested that patient plasma mitotane levels ≥14 g/ml lead to a 55-60% response rate, whereas those with lower levels have a low chance of response.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, significant side effects have generally only been observed in patients with plasma levels greater than 20 g/ml [7,10]. Plasma level monitoring of mitotane during treatment allows the more rapid attainment of a therapeutic plasma level (14-20 g/ml), as well as minimization of adverse effects due to an excessively high plasma level [9,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several dosing regimens have been proposed to achieve a plasma concentration between 14 and 20 mg L −1 . Low dosing regimens begin with 3 g per day for 3-4 months then continue with 1-2 g per day and allow to achieve the therapeutic range with manageable side effects in 3-5 months (European Medicines Agency, n.d.-a; Terzolo et al, 2000).…”
mentioning
confidence: 99%